Fiscal Decentralization and the Quality of Public Services in Russian Regions - Freinkman, Lev (2012)
The paper provides empirical analysis of the relationship between fiscal decentralization and the quality of public services in the Russian regions. The analysis suggests that fiscal decentralization has no significant effect on the key inputs into secondary education, such as schools, computers, or availability of pre-schooling, but has a significant positive effect on average examination results, controlling for the key observable inputs and regional government spending on education. Decentralization also has a positive impact on the quality of municipal utilities provision. Both effects can be attributed to strengthened fiscal incentives rather than to superior productive efficiency of municipal governments.